Students' Awareness of Gender Equality at SMK Negeri 3 Magelang - Fegasanti, Prahda Alifa (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2022)
Indonesia has come a long way in improving gender equality in access to education. Gender justice is linked to gender equality which occurs when men and female are treated equally. Gender equality demonstrates the same conditions and opportunities for both men and female to realize their rights and potentials without any discrimination. Schools are critical institutions for adapting students' perspectives, particularly when it comes to gender bias. As a result, gender-neutral schools that serve a strategic role and function in educating students for their multi-intelligence can grow effectively without being constrained by frequently gender-biased social beliefs. One of the goals of education is to teach students how to build a just society free of gender discrimination. This study is about the students' awareness towards gender equality in SMK Negeri 3 Magelang. This study aims to determine the level of students' understanding and their awareness of gender equality in their learning activities at school. The method used will be a qualitative phenomenological approach. While the instruments used will be in the form of observations and interviews with 50 students selected purposively to be participants in this study. The triangulation method will be applied in order to verify the data. The predicted findings of this study are that students will be aware of gender equality and will be helpful to minimize the occurrence of gender discrimination in the school environment. The result of this study proved that students are very aware of the concept of gender equality and are able to actualize it in activities at school without distinguishing gender.